2007
DOI: 10.1111/j.1442-2042.2007.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Percentages of positive cores, cancer length and Gleason grade 4/5 cancer in systematic sextant biopsy are all predictive of adverse pathology and biochemical failure after radical prostatectomy

Abstract: Aim:We investigated whether the quantitative parameters of systematic sextant biopsies were predictive of either adverse pathological findings or disease recurrence after radical prostatectomy (RP). Methods: We retrospectively evaluated a total of 117 men with untreated prostate cancer whose needle biopsies were matched with RP specimens. The pretreatment parameters of the serum prostate-specific antigen (PSA), the PSA density, the percentage of positive biopsy cores, the percentage of cancer length and the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
2
1
3
Order By: Relevance
“…Wills et al [18] determined that 89% of patients who had Gleason scores of six or less, number of positive cores two or less, and PSA levels lower than 4 ng/mL had organ-confined disease. However, the number of positive cores was not found to be a useful parameter for the prediction of adverse pathology and biochemical failure after RRP in various studies as it is in our study [9,10]. Recently, PPC in a prostate biopsy was thought to be a significant predictor of an adverse pathology and biochemical failure after RRP.…”
Section: Discussioncontrasting
confidence: 60%
“…Wills et al [18] determined that 89% of patients who had Gleason scores of six or less, number of positive cores two or less, and PSA levels lower than 4 ng/mL had organ-confined disease. However, the number of positive cores was not found to be a useful parameter for the prediction of adverse pathology and biochemical failure after RRP in various studies as it is in our study [9,10]. Recently, PPC in a prostate biopsy was thought to be a significant predictor of an adverse pathology and biochemical failure after RRP.…”
Section: Discussioncontrasting
confidence: 60%
“…Many previous reports mentioned that PSA at diagnosis, biopsy Gleason score, percent positive core, and clinical stage among the preoperative clinicopathological parameters were significant predictors of biochemical recurrence in the patients who underwent radical prostatectomy [4, 5, [8][9][10][11][13][14][15], while surgical Gleason score, ECE, PSM, and PNI were significant predictors among the postoperative pathological parameters [5,9,[16][17][18][19]. Our data showed that PSA at diagnosis, biopsy Gleason score, percent positive core, and PNI were significant predictive parameters of biochemical recurrence in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Com base nos achados, foi construída uma tabela contendo o nome dos autores e ano das publicações, assim como os dados sobre o número de pacientes, médias de idade, PSA e número de fragmentos colhidos na biópsia, e ainda um resumo dos principais resultados com suas significâncias estatísticas [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
Section: Resultsunclassified
“…Em 13 trabalhos 6,[8][9][10][11][17][18][19][20][21][22][23][24] , foi realizada avaliação uni e/ou multivariável do valor preditivo do PFA em relação aos achados patológicos da peça cirúrgica, e em todos os estudos, o PFA foi considerado como um excelente preditor do estágio cirúrgico.…”
Section: Resultsunclassified
See 1 more Smart Citation